2018
DOI: 10.1155/2018/1986982
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MDM2 via Nutlin-3A: A Potential Therapeutic Approach for Pleural Mesotheliomas with MDM2-Induced Inactivation of Wild-Type P53

Abstract: Previously, our group demonstrated that nuclear expression of E3 ubiquitin ligase (MDM2) in malignant pleural mesothelioma (MPM) is significantly associated with decreased overall survival. A possible explanation may be that overexpression of MDM2 leads to a proteasomal degradation of TP53 that eventually results in a loss of TP53-induced apoptosis and senescence. It is well known from other tumor entities that restoration of TP53 activity, e.g., by MDM2 inhibition, results in an instant TP53-induced stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…81 To restore p53 function, several small molecules, such as Nutlin-like drugs that interfere with MDM2/p53 interaction, were tested in journals.sagepub.com/home/tam 11 MPM. 82,83 In addition, NF2 has been shown to antagonize the inhibitory effect of MDM2 on p53, 84 and NF2-mutant MPM cells have been shown to be preferentially sensitive to anti-FAKtargeted therapy. 56 Consequently, co-targeting of FAK could improve MDM2-targeted therapy in MPM, probably through a coordinated mechanism that reactivates p53.…”
Section: Bap1 In Chromatin Modulationmentioning
confidence: 99%
“…81 To restore p53 function, several small molecules, such as Nutlin-like drugs that interfere with MDM2/p53 interaction, were tested in journals.sagepub.com/home/tam 11 MPM. 82,83 In addition, NF2 has been shown to antagonize the inhibitory effect of MDM2 on p53, 84 and NF2-mutant MPM cells have been shown to be preferentially sensitive to anti-FAKtargeted therapy. 56 Consequently, co-targeting of FAK could improve MDM2-targeted therapy in MPM, probably through a coordinated mechanism that reactivates p53.…”
Section: Bap1 In Chromatin Modulationmentioning
confidence: 99%
“…Overexpression of the ubiquitin ligase MDM2 in malignant pleural mesothelioma is negatively correlated with patient prognosis and leads to p53 degradation and decreased cisplatin Abbreviations: E1, ubiquitin-activating enzyme; E2, ubiquitin-conjugating enzyme; E3, ubiquitin ligase; WDHD1, WD repeat and HMG-box DNA binding protein 1; MAPRE2, microtubule-associated protein RP/EB family member 2; LUAD, lung adenocarcinoma; CO-IP, CO-immunocoprecipitation; IHC, immunohistochemical; PCR, polymerase chain reaction; siRNA, small interfering RNA. sensitivity (11). In addition, the ubiquitin ligase RNF31 is overexpressed in breast cancer tissues and MCF-7 cell lines, and it can promote polyubiquitination and degradation of p53 by stabilizing the ubiquitin ligase MDM2, which results in a reduction in cisplatin-induced apoptosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MDM2, a nuclear E3 ubiquitin ligase that binds and targets p53 for proteasomal degradation, is detected in 21.3% of clinical MPM samples, and its expression is significantly associated with poor survival [ 52 ]. To restore p53 function, several small molecules, such as the Nutlin-like drugs that disrupt MDM2/p53 interaction, have been tested in MPM [ 53 , 54 , 55 ]. Moreover, we and others have shown that the inactivation of CDKN2A/2B and TP53 is associated with an increased dependence on the G2/M checkpoint, which represents a targetable vulnerability in MPM [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%